An extended Petri net for modeling workflow with critical sections - Kotb, Yehia; Baumgart, André (IEEE International Conference on e-Business Engineering, 2005, 2005)
This work presents an extended workflow Petri net which synchronizes activity flow in the critical sections of the process. A critical section is a non empty set of tasks that cannot serve more than one activity at a time. The structure of the proposed net is introduced and a theorem is proposed and proved for the properties of separability and serializability. A fully detailed model for the operation theater in a hospital is presented using the proposed theoretical structure to control concurrency between activities in the critical sections.
Gesehen am 16.12.2019